Research progress and challenges in thermal maturity evalution of Lower Paleozoic source rocks - Xiaowei ZHENG; Fujie JIANG; Yu ZHANG; Jingqi ZHOU (Shiyou shiyan dizhi)
Marine source rocks in China's Lower Paleozoic are predominantly in the highly to over-mature stage. The lack of vitrinite in these strata has made thermal maturity evaluation a persistent technical challenge in deep hydrocarbon exploration. This study systematically summarizes organic matter maturity evaluation methods based on organic petrology, geochemistry, and spectroscopy, with the goal of assessing the applicability of various maturity parameters for highly to over-mature source rocks in the Lower Paleozoic, thereby providing insights for deep hydrocarbon resource exploration. Special emphasis is placed on analyzing graptolite reflectance, aromatic hydrocarbon molecular marker parameters, and Raman spectroscopy parameters, highlighting current challenges and future research directions. (1) Owing to its excellent thermal sensitivity, graptolite reflectance is extensively employed to characterize the maturity of Lower Paleozoic source rocks. Nevertheless, different graptolite types exhibit varying rates of reflectance increase, with "reflectance anomalies" observed within the gas window. (2) Aromatic hydrocarbon compounds (e.g., phenanthrene series and dibenzothiophenes) and their derived parameters (e.g., methylphenanthrene index MPI-1, and 4-MDBT/1-MDBT in methyldibenzothiophene) exhibit sensitive thermal stability responses, rendering them effective maturity evaluation parameters. However, their applicability might be constrained by the initial organic matter type and depositional environment. (3) Raman spectroscopy can effectively characterize molecular structure evolution and thermal maturity, through parameters derived from the D1 and G peaks. However, variations in laboratory instruments, wavelength selection, and spectral interpretation methods might limit comparability across studies. Finally, this study summarizes the theoretical foundations and practical applicability of these parameters, highlighting the impacts of mineral catalysis, radiation effects, and thermal simulation experiments on their suitability. The results demonstrate that a multi-parameter integrated approach significantly improves the accuracy of maturity evaluation. However, current calibration methodologies still require refinement to achieve optimal performance.